The Emerging Roles of Nicotinamide Adenine Dinucleotide Phosphate Oxidase 2 in Skeletal Muscle Redox Signaling and Metabolism - Cabello-Verrugio, C (Mary Ann Liebert Inc., 2019)
Significance: Skeletal muscle is a crucial tissue to whole-body locomotion and metabolic health. Reactive oxygen species (ROS) have emerged as intracellular messengers participating in both physiological and pathological adaptations in skeletal muscle. A complex interplay between ROS-producing enzymes and antioxidant networks exists in different subcellular compartments of mature skeletal muscle. Recent evidence suggests that nicotinamide adenine dinucleotide phosphate (NADPH) oxidases (NOXs) are a major source of contraction- and insulin-stimulated oxidants production, but they may paradoxically also contribute to muscle insulin resistance and atrophy. Recent Advances: Pharmacological and molecular biological tools, including redox-sensitive probes and transgenic mouse models, have generated novel insights into compartmentalized redox signaling and suggested that NOX2 contributes to redox control of skeletal muscle metabolism. Critical Issues: Major outstanding questions in skeletal muscle include where NOX2 activation occurs under different conditions in health and disease, how NOX2 activation is regulated, how superoxide/hydrogen peroxide generated by NOX2 reaches the cytosol, what the signaling mediators are downstream of NOX2, and the role of NOX2 for different physiological and pathophysiological processes. Future Directions: Future research should utilize and expand the current redox-signaling toolbox to clarify the NOX2-dependent mechanisms in skeletal muscle and determine whether the proposed functions of NOX2 in cells and animal models are conserved into humans. © Copyright 2019, Mary Ann Liebert, Inc., publishers 2019.